The impact of spiritual intelligence on work performance : Case studies in government hospitals of east coast of Malaysia - Anita, Abdul Rani; Imaduddin, Abidin; Mohd Rashid, Abdul Hamid (Macrotheme, 2013)
This study examined the causal relationship of spiritual intelligence on work performance among the staff nurses at three states of Malaysia i.e. Pahang, Terengganu and Kelantan. Questionnaires were developed and distributed to staff at the selected Government Hospitals which involved 506 female respondents in the age of 20-45 years old. The data collected was analysed using confirmatory factor analytic (CFA) approach and fullfledged structural equation modeling (SEM) in order to test the hypothesized model of the impact of Spiritual Intelligence on Work Performance. In addition, invariance analysis was also conducted on the demographic moderator such as age and tenure. The revised hypothesized SEM model yielded a p-value = 0.000, normed chi-square=3.999, CFI=0.972, TLI=0.963, GFI=0.939 and RMSEA=0.077. From the result, it can be found that work performance is influenced by Spiritual Intelligence. Also, the moderating factor of age and tenure is not significant that the model is applicable to all hospitals involved. This finding may pave the way forward for empowering spiritual intelligence in nursing school and training to enhance nurse’s work performance.